Correction: Unraveling variation on the profile aroma compounds of strong aroma type of Baijiu in different regions by molecular matrix analysis and olfactory analysis. Issue 54 (29th October 2021) - Hong, Jiaxin; Wang, Junshan; Zhang, Chunsheng; Zhao, Zhigang; Tian, Wenjing; Wu, Yashuai; Chen, Hao; Zhao, Dongrui; Sun, Jinyuan
Abstract : Correction for 'Unraveling variation on the profile aroma compounds of strong aroma type of Baijiu in different regions by molecular matrix analysis and olfactory analysis' by Jiaxin Hong et al., RSC Adv., 2021, 11, 33511–33521. DOI: ; 10.1039/D1RA06073B .